RECENT TRENDS IN INDUSTRIAL INVESTMENT INMANUFACTURING SECTOR IN TAMIL NADU - P T, Listin (International Journal of Psychosocial Rehabilitation, 2020)
Industrial investment plays a considerable role in economic growth, as it stimulates positively domestic investments, employment generation, skill development and technology. A strong infrastructure is an indispensable factor for any manufacturing sector. The expansion of industrial sector plays a crucial role in economic upliftment. Traditionally, Tamil Nadu has been always in the vanguard of industrialisation with a strong presence in the manufacture of engineering and auto components, textiles, leather, sugar and the like. Countries like India have started to provide various incentives in order to attract industrial investment. The manufacturing sector attracted significant amount of FDI in the past fifteen years of which a major chunk accrued to technology intensive sectors, while the labour intensive ones received negligible inflows. Unlike loans, FDI can bring enlargement of capital without reimbursement commitments and uniquely potent bundle of capital, contacts, managerial and technical knowledge with potential benefit of host country firms. Tamil Nadu continues to be safe haven for the investors owing to ideal business climate and healthy socio economic conditions. In this paper, manufacturing sector has been divided into various subsectors for analyzing its trend. Further, the trends of FDI inflow into the sector are projected for a period from 2010-2011to 2019- 2020 using trend analysis.